Avaliação de um coletor magnético de metaloproteinases na adesão e alteracão dentinária - Zenobi, Walter (2018)
The aim of the present study was to evaluate the effects of the application of a new magnetic collector of matrix metalloproteinases (MMPs) to the dentin prior to the application of the adhesive and to analyze the adhesion and removal of MMPs from dentin collagen mesh. The magnetic collector was incorporated in a gel at 2% and 20% concentration. In addition, a standardized gel without substances that interact with MMPs and a gel with 2% chlorhexidine digluconate were used as negative and positive controlrespectively. Dentin specimens were bonded with Prime & Bond 2.1 adhesive (Dentsply) after application of 37% phosphoric acid gel. Bonded teeth (n=5) were cut and evaluated by the microtensile bond strength test after 24h immersed in distilled water. To evaluate the presence / removal of MMPs, dentin specimens (n=10) were prepared and the collector was applied with and without the use of magnet to evaluate the presence of MMPs in the dentin with ferrite nanoparticles anchored in the enzymes observed in electron microscopy (SEM) with confirmation by energy dispersive X-ray spectroscopy(EDS). Data were statistically analyzed by one-way ANOVA and Tukey’s post-hoc test. The level of significance was 5%. Metalloproteinases magnetic collector (MMC) incorporated in a gel at 2% and 20% concentration applied to the dentin prior to the application of the adhesive did not interfere with the initial adhesion (p=0.432) and the MMPs in the dentin were reduced from 0,3% to 0.0% only with the use of the magnet after the collector. It is concluded that the proposed MMPs magnetic collector has an effective action on the removal of MMPs, without altering the adhesion to dentin.